Addiction in Adolescence: Why don't adolescent addicts turn up for treatment? - Griffiths, Mark; Chevalier, Serge (Psyke & Logos, 2005)
It has been well established that prevalence rates of addiction are reportedly higher among youth than adults. It is also widely reported that very few adolescent addicts turn up for treatment. This paper outlines some of the possible reasons as to why this is the case. These are that (i) adolescents don’t seek treatment in general, (ii) treating other underlying problems may help adolescent addiction problems, (iii) attending treatment programs may be stigmatizing for adolescents, (iv) adolescents may have committed suicide before getting treatment, (v) addicts may be lying or distorting the truth when they fill out survey questionnaires, (vi) adolescents may not understand what they are asked in questionnaires, (vii) screening instruments for adolescent addicts may be being used incorrectly, (viii) adolescent addiction may be socially constructed to be non-problematic and (ix) adolescent excesses may change too quickly to warrant treatment.